Новые данные по систематике и географическому распространению мух-стволоедок (Diptera, Xylophagidae) - Кривошеина, Н.П.; Мамаев, Б.М. (Вестник зоологии, 1982)
The new distributional data are given for Palearctic dipterans of the genus Xylopha- gus Mg. Xylophagid larvae are well known predators of wood-dwelling insects develop- ing on different tree species. X. caucasicus sp. n., closely related to X. compeditis M g . , is described from the Northern Caucasus (Krasnodar Territory) and Azerbaiian. It differs from X.compeditus byhead and metapleural pubescence, its larvae develop underthe bark of deciduous and coniferous trees. Holotype is deposited at the Institute of Evolutionary Animal Morphology and Ecology (Moscow), paratype at the Zoological Institute, USSR. Academy of Sciences (Leningrad).